Research and Optimization of RR&P5R Decoupled Parallel Mechanism with a Fully Spherical Workspace - Yu Shanshan; Zhang Jianjun; Li Weimin; Yang Xianhai (Jixie chuandong)
Spherical parallel mechanisms with large or fully spherical workspace are one of the important research directions in the application of large-angle workspace. Aiming at the problem of insufficient workspace in the current spherical parallel mechanisms，a new idea for the type design of a 2-DOF decoupled parallel mechanism with a fully spherical workspace is presented based on the input and output characteristics of the double rocker mechanism. And a newly decoupled parallel mechanism (RR&P5R) with a fully spherical workspace is designed. The kinematic equations of parallel mechanism are established through kinematic analysis. Then the relationship of displacement，velocity and acceleration between input and output for the RR&P5R mechanism are obtained. With the objective of the minimum input quantity q2，the size of the RR&P5R mechanism is optimized. This research provides an important theoretical basis for large-angle spherical workspace applications.